Advanced stage (IIIC/IV) endometrial cancer: Role of cytoreduction and determinants of survival. (March 2019) - Rajkumar, Savithri; Nath, Rahul; Lane, Geoffrey; Mehra, Gautam; Begum, Shahina; Sayasneh, Ahmad
Highlights: Optimal cytoreduction leads to improved survival in advanced uterine cancer. 85% of long- term survivors (>36 months) have undergone optimal cytoreduction. Significant predictors of survival are cytoreductive status, performance status and presence of bowel disease. Abstract: Objective: Primary aim of this study was to assess the impact of optimal cytoreduction in women who had surgical treatment of advanced stage (IIIC/IV) endometrial cancer. Secondary objective was to define demographic and surgico-pathologic variables that exerted a significant influence on survival outcomes. Study design: Records of 45 patients with stage IIIC/IV Endometrial cancer who underwent surgery with cytoreductive intent between 2010 and 2016 were analysed. Data on disease distribution, surgical procedures, adjuvant therapy and survival times was collated. Survival curves were plotted by Kaplan Meier method and median survival estimates were compared using log rank test. Cox proportional hazards model was used to identify independent variables predictive of survival. Results: 28 women (62.2%) had undergone primary surgery and 17 (37.8%) received neoadjuvant chemotherapy prior to delayed primary surgery. Optimal cytoreduction to </ = 1 cm visible disease was achieved in 29 women (64.4%). Among 29 women who had optimal debulking, 24 had no visible disease. Median overall survival for the entire study cohort was 24 months. Median progression free survival in the optimal cytoreduction group was 16 months as opposed to 11.5 months in women who had > 1 cm residual disease (p = 0.02). Median overall survival was 29 months in patients who had optimal cytoreduction and 17.5 months in women who had bulky residual disease (p=0.002). Only poor performance status (p = 0.035), presence of bowel disease (p = 0.05) and suboptimal cytoreduction (p = 0.006) retained significance as predictors of poor survival on multivariate analyses. Suboptimal cytoreduction surgery, compared to optimal cytoreduction, showed a 3.55-fold increased risk of death independent of performance status and anatomic region with disease (Hazard Ratio 3.55 (95% confidence interval 1.44–8.73) p = 0.006). Conclusion: Survival analyses demonstrate significantly better progression free survival and overall survival when optimal cytoreduction is achieved. A prospective, multicentre study is recommended to establish conclusive evidence.